2021
DOI: 10.3390/molecules26216378
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ions into Nanostructured Anodic Oxides—Mechanism and Functionalities

Abstract: Anodic oxidation of metals leads to the formation of ordered nanoporous or nanotubular oxide layers that contribute to numerous existing and emerging applications. However, there are still numerous fundamental aspects of anodizing that have to be well understood and require deeper understanding. Anodization of metals is accompanied by the inevitable phenomenon of anion incorporation, which is discussed in detail in this review. Additionally, the influence of anion incorporation into anodic alumina and its impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 173 publications
(205 reference statements)
0
13
0
Order By: Relevance
“…50 Typically, the amount of anionic contaminants decrease in the anodic Al 2 O 3 formed in electrolytes follows the order of H 2 SO 4 4 H 3 PO 4 4 H 2 C 2 O 4 . 88,97 The photoluminescence spectra acquired by Yamamoto et al revealed three layers in the chemical composition of NAA, with a decrease of impurities across the outer, middle and inner region of oxide pore walls (Fig. 5a-ii).…”
Section: Chemical Properties Of Naamentioning
confidence: 95%
See 1 more Smart Citation
“…50 Typically, the amount of anionic contaminants decrease in the anodic Al 2 O 3 formed in electrolytes follows the order of H 2 SO 4 4 H 3 PO 4 4 H 2 C 2 O 4 . 88,97 The photoluminescence spectra acquired by Yamamoto et al revealed three layers in the chemical composition of NAA, with a decrease of impurities across the outer, middle and inner region of oxide pore walls (Fig. 5a-ii).…”
Section: Chemical Properties Of Naamentioning
confidence: 95%
“…Due to their larger ionic radii and lower mobility, electrolytic anions migrate across the BOL at lower velocity during the electric field-assisted growth of anodic oxide. [88][89][90][91][92][93] This results in a duplex structure of anodic oxide: inner layers composed of pure Al 2 O 3 and outer layers that are contaminated with electrolytic anions. [94][95][96] pure alumina in porous anodic oxide layer to the strength of electric field applied during anodization and their transmission electron microscopy analysis of ion-beam thinned porous anodic films revealed the existence of cell boundary bands in the pore wall oxide produced in different electrolytes.…”
Section: Chemical Properties Of Naamentioning
confidence: 99%
“…The anion content of porous anodic films linearly increases with the increasing log of the current density, i.e., electric field strength [ 15 ], similar to the case of barrier-type films [ 17 , 19 , 59 ]. It is shown that the anion content and species significantly affect the film properties [ 23 , 36 , 68 , 71 , 72 , 73 ]. In barrier-type films, the anion species and the content of anions have a significant impact on the permittivity, as well as the leakage current, due to the formation of defects [ 17 , 18 , 19 , 74 , 75 ].…”
Section: Incorporation Depth and Content Of Electrolyte Anionsmentioning
confidence: 99%
“…Over the years, numerous studies have been conducted to optimize the properties of the surface oxide layer to promote implant osseointegration. Anodic oxidation is a widely used method for this purpose because it allows, through appropriate choice of anodizing conditions, to improve the passivation of the metal by growing thick oxide films enriched in osteoconductive elements, such as Ca and P, with a highly porous structure, which favors osseointegration [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%